2021
DOI: 10.1556/030.2021.01526
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory parameters predicting mortality of adult in-patients with COVID-19 associated cytokine release syndrome treated with high-dose tocilizumab

Abstract: Large randomized clinical trials in severe Coronavirus Disease 2019 (COVID-19) patients have proven efficacy of intravenous tocilizumab. Our aim was to describe the laboratory parameters predicting in-hospital mortality of patients with tocilizumab administration in COVID-19 associated cytokine release syndrome (CRS).We evaluated high-dose (8 mg/kg) intravenous tocilizumab administration in severe and critically ill COVID-19 adult patients fulfilling predefined strict CRS criteria. A single-centre, prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Literature evidence shows that poor outcome is associated with persistence of high biomarkers values after Tocilizumab administration. Lakatos B et al, in a one hundred and six sample size study on COVID-19 patients treated with Tocilizumab, reported that patients who died had higher values of IL-6 and LDH and insufficient restoration of lymphocytes count at 7 and 14 days after Tocilizumab administration compared with survivors [35] . A lot of evidence shows that different phenotypes of COVID-19 patients with different inflammatory and immune response, mortality risk and response to respiratory support exist [4] , [36] , [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Literature evidence shows that poor outcome is associated with persistence of high biomarkers values after Tocilizumab administration. Lakatos B et al, in a one hundred and six sample size study on COVID-19 patients treated with Tocilizumab, reported that patients who died had higher values of IL-6 and LDH and insufficient restoration of lymphocytes count at 7 and 14 days after Tocilizumab administration compared with survivors [35] . A lot of evidence shows that different phenotypes of COVID-19 patients with different inflammatory and immune response, mortality risk and response to respiratory support exist [4] , [36] , [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, monitoring these parameters during hospitalisation of the patient on tocilizumab treatment would be the key to see if there is a beneficial response or, on the contrary, an increased risk of mortality. The scientific evidence concludes that a poor outcome is associated with persistently high biomarker values over time after tocilizumab administration, such as LDH, IL-6 and low absolute lymphocyte counts [ 56 ]. To circumvent this problem, and due to the large subject-to-subject variability in response to anti-inflammatory treatment for COVID-19, personalized strategies are being developed, guided by rapid cytokine assays, such as the digital immunoassay, which allows rapid “real-time” cytokine monitoring [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…To tail treatment on single patient based on his or her inflammatory status could improve the rate of success, as highlighted by Levi M in a recent issue of European Journal of Internal Medicine [2] . Evidence shows that the response to TCZ in this context is associated with restoration of thrombo-inflammation biomarkers after its administration [3] , while persistence of high biomarkers after TCZ administration seems to be associated with poor outcome [4] . Recently, Emre Eskazan A. et al.…”
Section: Dear Editormentioning
confidence: 99%